ANALISIS AKUNTABILITAS DAN PELAPORAN HIBAH PADA BIRO KSEJAHTERAAN RAKYAT DI KANTOR GUBERNUR SUMATERA UTARA - Lannida, Nida (Jurusan Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Tanjungpura, 2024)
Abstrak : An award is a guide that doesn't need to be returned and isn't restricting on a specific party's gift. The arrangement of cash, labor and products should have a drawn out sway and should in any case focus on the autonomy of the country and state. States can likewise give awards to legislatures from different nations, global associations, nearby legislatures, organizations, foundations or networks with the end goal of compassionate fortitude, government assistance improvement and monetary and social purposes. This study expects to decide the responsibility and detailing of awards through a writing study, namely analyzing existing regulations to find out how grant accounting and reporting practices can be applied to the central government and local governments. Accounting responsibility for transactions consists of recognition, measurement, and presentation and achievement. Grants can be categorized into grant income and grant expenditure/expense. Grants in the manuscript of. The. Grant. agreement betweenn the. Giver. andd thee recipientt off.the. grantt with no compensation or remunerationKeywords: grant, accounting practice, grant reporting